EFEKTIVITAS ASAM ASKORBAT DALAM EKSTRAK BUAH TOMAT (Lycopersicon esculentum Mill.) TERHADAP PEMUTIHAN GIGI DENGAN KONSENTRASI 30%, 70%, DAN 100% - Mala, Hilma Falhil; Arti, Dwi Windu Kinanti; Aprillia, Zita (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Introduction : Dental discoloration reduces the beauty of someone's appearance. The changing color of teeth can be doneÂ  by bleaching treatment with natural ingredients. The purpose of this study is to determine the effectiveness of ascorbic acid in tomato extract (Lycopersicon esculentum Mill.) to teeth whitening with concentrations of 30%, 70%, and 100%. Method : This research type is pretest-postestgroup design. The sample used 27 premolar post- extraction teeth soaked with black tea for 6 days then soaked with ascorbic acid in tomato extract concentration 30%, 70% and 100% for 3 days. The measurement of teeth color uses spectrophotometer. The data analyzing uses Kruskal-Wallis different test and further test of Post Hoc Mann-Whitney. Result : The result of Kruskal-Wallis different test shows that p = 0,010 (p <0,05) means that there is difference between before and after immersion of ascorbic acid in tomato extract with concentration 30%, 70%, and 100%. Based on the results of the Mann-Whitney Post Hoc test, the difference between 30% and 100% concentrations has a value of p = 0.009 (p <0.05) most effective than the difference between 30% and 70% concentrations and thedifference between 70% and 100% concentrations. Conclusion : Ascorbic acid in tomato extract (Lycopersicon esculentum Mill.) with concentrations of 30%, 70%, and 100% effective in teeth whitening. Keywords: bleaching, ascorbic acid, tomato extract, spectrophotometer